Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Pada Biro Pemerintahan Setda Provinsi Jambi - Sudirman Sudirman; Ubaidillah Ubaidillah (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Human resource management is one of the fields of general management which includes aspects of planning, organizing, implementing, and controlling. This process is found in the fields of production, marketing, finance, or staffing. Because human resources are considered to be increasingly important role in achieving company goals, various experiences and results of research in the HR field are systematically collected in what is called human resource management. The term "management has the meaning of knowledge about how to manage human resources.